2014
DOI: 10.1161/circresaha.114.302293
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Na + /K + ATPase α2 But Not α1 Isoform Attenuates Pathological Cardiac Hypertrophy and Remodeling

Abstract: Rationale The Na+/K+ ATPase (NKA) directly regulates intracellular Na+ levels, which in turn indirectly regulates Ca2+ levels by proximally controlling flux through the Na+/Ca2+ exchanger (NCX1). Elevated Na+ levels have been reported during heart failure, which permits some degree of reverse mode Ca2+ entry through NCX1, as well as less efficient Ca2+ clearance. Objective To determine if maintaining lower intracellular Na+ levels by NKA overexpression in the heart would enhance forward-mode Ca2+ clearance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 43 publications
(53 reference statements)
6
68
1
Order By: Relevance
“…Furthermore, replacement of endogenous ouabain-resistant ␣1 with a ouabain-sensitive ␣1 mutant increases both cardiac hypertrophy and fibrosis in pressure-overload models (49). In addition, transgenic overexpression of Na-K-ATPase ␣2 but nor ␣1 attenuated pressureoverload-induced cardiac hypertrophy in a recent study by Correll et al (9). Retrospectively, these in vivo findings are consistent with our new data, indicating that ␣1 is most likely responsible for cardiotonic steroid-induced fibrosis of the heart whereas ␣2, predominantly involved in ion transport, may protect the heart from pressure-overload-induced hypertrophy.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, replacement of endogenous ouabain-resistant ␣1 with a ouabain-sensitive ␣1 mutant increases both cardiac hypertrophy and fibrosis in pressure-overload models (49). In addition, transgenic overexpression of Na-K-ATPase ␣2 but nor ␣1 attenuated pressureoverload-induced cardiac hypertrophy in a recent study by Correll et al (9). Retrospectively, these in vivo findings are consistent with our new data, indicating that ␣1 is most likely responsible for cardiotonic steroid-induced fibrosis of the heart whereas ␣2, predominantly involved in ion transport, may protect the heart from pressure-overload-induced hypertrophy.…”
Section: Discussionmentioning
confidence: 96%
“…Retrospectively, these in vivo findings are consistent with our new data, indicating that ␣1 is most likely responsible for cardiotonic steroid-induced fibrosis of the heart whereas ␣2, predominantly involved in ion transport, may protect the heart from pressure-overload-induced hypertrophy. Indeed, overexpression studies strongly suggested that ␣2-mediated protection was promoted through its ability to promote Ca 2ϩ clearance by NCX1 more efficiently than its ␣1 counterpart, rather than through a modulation of the hypertrophic signaling (9). Second, it is important to note that the ␣1 isoform is expressed ubiquitously whereas the ␣2 isoform is primarily found in myocytes.…”
Section: Discussionmentioning
confidence: 99%
“…8–12 week old mice (C57/BL/6J) were subjected to TAC or sham surgical procedure to induce chronic left ventricular pressure overload as described previously [13]. The animals were anesthetized with 1.5% isoflurane, intubated, and ventilated with a volume-cycled rodent respirator.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Correll et al show by overexpressing α1 and α2 tg mice, that only overexpression of α2 subunits of the Na + /K + -ATPase reduced cardiac hypertrophy and remodeling [50]. Furthermore, distribution of α1 and α2 isoforms varies in heart in a region-specific manner [51], even in the same single cell [52].…”
Section: Dzurba Et Al Reported That Pretreatment Of Ovariectomized Fmentioning
confidence: 99%